Research on modelling and simulation for dynamic characteristics of magnetic shaft coupling. (2017) - Meng, Zhuo; Lu, Wei; Meng, Ziyi; Sun, Yize; Zhu, Helei
This paper investigates the dynamic characteristics of magnetic shaft coupling by modelling and simulation. A dynamic model of magnetic shaft coupling is developed and simplified by linearisation at the equilibrium point of steady state. The simulation results indicate that magnetic shaft coupling could lessen mechanical shock during starting process. The linearisation error is computed and analysed. The dynamic block-diagram of the linearised model is simplified and arranged, and then a typical second order oscillating system is achieved. Further, the dynamic characteristics of the oscillating system are discussed.